3x(a-7b)-10y(a-7b)=

Simple and best practice solution for 3x(a-7b)-10y(a-7b)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(a-7b)-10y(a-7b)= equation:


Simplifying
3x(a + -7b) + -10y(a + -7b) = 0
(a * 3x + -7b * 3x) + -10y(a + -7b) = 0
(3ax + -21bx) + -10y(a + -7b) = 0
3ax + -21bx + (a * -10y + -7b * -10y) = 0
3ax + -21bx + (-10ay + 70by) = 0

Reorder the terms:
3ax + -10ay + -21bx + 70by = 0

Solving
3ax + -10ay + -21bx + 70by = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '21bx' to each side of the equation.
3ax + -10ay + -21bx + 21bx + 70by = 0 + 21bx

Combine like terms: -21bx + 21bx = 0
3ax + -10ay + 0 + 70by = 0 + 21bx
3ax + -10ay + 70by = 0 + 21bx
Remove the zero:
3ax + -10ay + 70by = 21bx

Add '-70by' to each side of the equation.
3ax + -10ay + 70by + -70by = 21bx + -70by

Combine like terms: 70by + -70by = 0
3ax + -10ay + 0 = 21bx + -70by
3ax + -10ay = 21bx + -70by

Reorder the terms:
3ax + -10ay + -21bx + 70by = 21bx + -21bx + -70by + 70by

Combine like terms: 21bx + -21bx = 0
3ax + -10ay + -21bx + 70by = 0 + -70by + 70by
3ax + -10ay + -21bx + 70by = -70by + 70by

Combine like terms: -70by + 70by = 0
3ax + -10ay + -21bx + 70by = 0

The solution to this equation could not be determined.

See similar equations:

| 1/2x×-4= | | 1/3x×-4=7 | | 10a+2b+b=100 | | 8(20-x)=5x | | 2cos(x)-5sin(x)=0 | | x^2+30x=-150 | | (y^2)+4y-192=0 | | 2=1/2b | | 6y^3-11y^2=6y^2+3y | | 4x^3-12x^2-20x= | | 60x^3-42x^5= | | 6-5x=-x-14 | | y^2-48x+8y-128=0 | | 6(-9+4x)=42 | | 42+2x=x | | 42+2y=x | | 28x^6-63x^5= | | 14nmp-5mpn= | | 42=x-2y | | 2ab+3ba= | | -2x-5=6x-77 | | z=40x+20y | | (2x-5)=2(x+2) | | x+48(yx^2-2)=20 | | 6x+9+x=-12 | | 7x+2+4x=46 | | x/3-7=1 | | 2cd^2-2dc^2=0 | | 2y+120=x+78 | | 12x+y=42 | | 2(4x+1)=58 | | 2log(4x-80)=4.6 |

Equations solver categories